Pyrrolidinyl Group as Charge Donor for the Excited State Intramolecular Chargetransferin 3-(4-methoxyphenyl)-1-(4-(pyrrolidin-1-yl) phenyl) Prop-2-en-1-one - Mishra, Nidhi; Chaudhary, Kamal Kumar; Awasthi, Satish Kumar (Journal of Applied Solution Chemistry and Modeling, 2015)
The absorption and steady state emission properties of a chemically synthesized chalcone, 3-(4-methoxyphenyl)-1-(4-(pyrrolidin-1-yl) phenyl) prop-2-en-1-one (MPPP) containing asymmetrical donor and acceptor groups has been investigated both experimentally and theoretically. The ground state, MPPP has a significant intramolecular charge transfer (ICT) character and a great sensitivity to the hydrogen bond donating ability of the medium as reflected from the absorption spectra in pure non polar, polar and neutral solvents. On the other hand, its excited singlet state exhibits high ICT characters as manifested by the drastic solvatochromic effects. These results are consistent with the data. The absorption spectra of the compound MPPP undergoes minor changes with increasing polarity of the solvents and the fluorescence spectra experiences a distinct bathochromic shifts in the both position and fluorescence quantum yields, increases reaching a maximum before decrease with increasing the solvent effects. The quantum yields decrease with increase in the solvent polarity. The magnitude of change in the dipole moment was also calculated using Austin Model 1 (AM1). These results suggest that the evidence about the intramolecular charge transfer in the emitting singlet state of this compound. The solvent dependence of quantum yields of MPPP was interpreted on the basis of positive and negative solvatokinetic as well as hydrogen bonding effects. Intramolecular charge (ICT) transfer took place from pyrrolidine nitrogen to α, β unsaturated carbonyl in the ground state.